Peranan Ikatan Remaja Masjid Raya Sunur dalam Meningkatkan Kesadaran Beragama - Rezi Yuhanda Nasdi; Indah Muliati (Prodi Pendidikan Keagamaan Islam, 2022)
This research is motivated by an interest in the role of mosque youth in increasing the religious awareness of teenagers in Sunur Tengah. Nan Patient District, Padang Pariaman Regency. Because the youth of the Middle Sunur Mosque has played a role and provided a positive influence, it is evident from the teenagers of Central Sunur who diligently pray in congregation at the mosque, the teenagers are diligent in attending weekly wirid studies, guiding children to recite the dawn education and a sense of caring and polite attitude with the surrounding community. This study aims to examine: first, to describe how the mosque's Youth Program increases the religious awareness of teenagers in Sunur Tengah, and second, to describe the role of mosque youth in increasing awareness of religious youth in Sunur Tengah. The third is to describe the supporting factors and inhibiting factors for the mosque youth program. This research is a type of field research using qualitative methods. The results showed that the mosque's youth program, (1) Tadarus tahsin Alquran, (2) weekly wirid studies, (3) taught TPA children at dawn, and (4) cadre of mosque youth by implementing the mosque youth program.